Idea Europy Środkowej w eseistyce Andrzeja Stasiuka i Jurija Andruchowycza - Kalina, Arkadiusz (Slavia Occidentalis, 2011)
The article analyses the Central European issues in the work of two popular and highly regarded writers: Ukrainian – Yuri Andrukhovych, and Polish – Andrzej Stasiuk. Both authors, in an original way, looked to the old idea of Central Europe (Mitteleuropa) and to its presentation after the Second World War. Despite many similarities between the concepts of both writers, there are significant differences that result from the otherness of national traditions, literary dispositions and artistic references to the sphere of myth.